Frequency and reasons for missed appointments of outpatient mental health care users in the uMgungundlovu District - Lucelle Ramlucken; Maureen N. Sibiya (AOSIS, 2018)
Background: Over the years, there has been a rapid growth in the use of mobile technology which has been proven to increase treatment adherence. Short message services may improve service delivery through appointment reminders and improve communication between health care workers and patients. Missed appointments are becoming common amongst mental health care users, and this has a significant economic burden on mental health symptoms. Objectives: The aim of the study was to determine the frequency and reasons for missed appointments of outpatient mental health care users for their follow-up care in the uMgungundlovu District. Method: This study used a quantitative survey. A non-probability convenient sampling method was used to select 182 participants at the psychiatric clinics. Results: Of the 182 participants, results of the study indicated that n = 84 (46.2%) respondents had missed their appointment at some stage. Of the n = 84 (46.2%) respondents who had missed appointments, n = 28 (33.3%) had missed their appointment once, and n = 45 (53.6%) had missed their appointment 2-3 times. Most common reasons for missed appointments included mental health care users forgetting (n = 58; 69%), work commitments (n = 14; 16.7%), no transportation (n = 4; 4.8%) and financial constraints (n = 5; 6%). Conclusion: The main reasons for missed appointments that were identified included forgetfulness, work commitments, lack of transportation and financial constraints. A significant number of participants (53.6%) had missed their appointments 2-3 times.